Analysis of Customer Satisfaction and Loyalty Using BRImo - Mohammad Sofyan; Alian Natision; Tung Tran Minh; Teguh Santoso (Yayasan Ilomata, 2022)
This research aims to analyze the customer satisfaction of BRImo app users. Descriptive qualitative research design describes systematically and accurately the facts and characteristics of customer satisfaction and loyalty of BRImo app users. The results showed that dominant customers were also satisfied and were most likely to tell positive things about the BRImo application. Bank BRI needs to evaluate customers who feel dissatisfied and disloyal.